Production interdependence and welfare - Kevin X. D. Huang; Zheng Liu (European Central Bank (ECB), 2004)
The international welfare effects of a country's monetary policy shocks have been controversial in the new open economy macro (i.e., NOEM) literature. While a unilateral monetary expansion increases the production efficiency in each country, it affects the terms of trade in favor of one country against another depending on the currencies of price setting. In this paper, we incorporate multiple stages of production and trade into a standard NEOM model to capture world production interdependence, and show that increased world production interdependence tends to magnify the e±ciency-improvement effect while dampening the terms-of-trade effect. As a consequence, a unilateral monetary expansion can be mutually beneficial regardless of in which currency prices are set. In this sense, international monetary policy transmission may not be a source of potential conflict in a world with production interdependence.
Keywords: E32; F31; F41; 330; Local currency pricing; Monopolistic competition; Stages of processing; Welfare